Pharmacological Inhibition of STAT6 Ameliorates Myeloid Fibroblast Activation and Alternative Macrophage Polarization in Renal Fibrosis - Jiao, Baihai; An, Changlong; Tran, Melanie; Du, Hao; Wang, Penghua; Zhou, Dong; Wang, Yanlin (Frontiers in Immunology, 2021)
A hallmark of chronic kidney disease is renal fibrosis, which can result in progressive loss of kidney function. Currently, there is no effective therapy for renal fibrosis. Therefore, there is an urgent need to identify potential drug targets for renal fibrosis. In this study, we examined the effect of a selective STAT6 inhibitor, AS1517499, on myeloid fibroblast activation, macrophage polarization, and development of renal fibrosis in two experimental murine models. To investigate the effect of STAT6 inhibition on myeloid fibroblast activation, macrophage polarization, and kidney fibrosis, wild-type mice were subjected to unilateral ureteral obstruction or folic acid administration and treated with AS1517499. Mice treated with vehicle were used as control. At the end of experiments, kidneys were harvested for analysis of myeloid fibroblast activation, macrophage polarization, and renal fibrosis and function. Unilateral ureteral obstruction or folic acid administration induced STAT6 activation in interstitial cells of the kidney, which was significantly abolished by AS1517499 treatment. Mice treated with AS1517499 accumulated fewer myeloid fibroblasts and myofibroblasts in the kidney with ureteral obstruction or folic acid nephropathy compared with vehicle-treated mice. Moreover, AS1517499 significantly suppressed M2 macrophage polarization in the injured kidney. Furthermore, AS1517499 markedly reduced the expression levels of extracellular matrix proteins, and development of kidney fibrosis and dysfunction. These findings suggest that AS1517499 inhibits STAT6 activation, suppresses myeloid fibroblast activation, reduces M2 macrophage polarization, attenuates extracellular matrix protein production, and preserves kidney function. Therefore, targeting STAT6 with AS1517499 is a novel therapeutic approach for chronic kidney disease.